Allyl Syringate - Thimpa, Naruedech; Poprom, Suriyaphong; Songpao, Laksakarn; Chotsaeng, Nawasit (My University, 2025)
Syringic acid (1) is a naturally occurring compound with diverse biological activities. Structural modification of syringic acid often enhances its utility; however, the spectroscopic data for several derivatives remain unreported, and the procedures to obtain them can be synthetically challenging. In this study, we report the allylation of syringic acid (1) to afford a novel derivative, allyl syringate (1c). The structure of this compound was confirmed by IR, NMR, and MS spectroscopy and compared with those of closely related derivatives (1a and 1b). These findings provide a useful foundation for further studies on the allylation of syringic acid and related phenolic acid derivatives.
Keywords: allyl bromide; allyl syringate; allylation; syringic acid